2013
DOI: 10.1021/la400155d
|View full text |Cite
|
Sign up to set email alerts
|

Patterned Polymer Films via Reactive Silane Infusion-Induced Wrinkling

Abstract: A method for simultaneously patterning and functionalizing thin poly(2-hydroxyethyl methacrylate) films through a reactive silane infusion based wrinkling is developed. Wrinkled patterns with tunable wavelengths on submicrometer size are easily produced over large area surfaces and can express a wide variety of chemical functional groups on the surface. The characteristic wavelength of wrinkling scales linearly with initial film thickness, in agreement with a gradationally swollen film model. Results from X-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 58 publications
1
32
0
Order By: Relevance
“…We demonstrated that the morphology and properties of the skin layers can be controlled by adjusting both the process conditions and substrates topography, and that the skin layers significantly reduce the solvent/gas permeation and improve the gas selectivity. Different from the reactive infusion process where a reactive silane diffuse and covalently bounded to the network, 37 the infiltrated polyamide is physically fused with the PDMS network within the skin layer. Thus, the GLIP processes is extremely versatile: the infiltrated polymers can be selected from a broad range of interfacial polymerization systems, 38 and the substrates can be any polymer networks.…”
Section: Discussionmentioning
confidence: 99%
“…We demonstrated that the morphology and properties of the skin layers can be controlled by adjusting both the process conditions and substrates topography, and that the skin layers significantly reduce the solvent/gas permeation and improve the gas selectivity. Different from the reactive infusion process where a reactive silane diffuse and covalently bounded to the network, 37 the infiltrated polyamide is physically fused with the PDMS network within the skin layer. Thus, the GLIP processes is extremely versatile: the infiltrated polymers can be selected from a broad range of interfacial polymerization systems, 38 and the substrates can be any polymer networks.…”
Section: Discussionmentioning
confidence: 99%
“…2-hydroxyethyl methacrylate (98%) were purchased from Acros Organics and Poly(2-hydroxymethyl methacrylate) (PHEMA) was synthesized according to our previous work. 23 …”
Section: Methodsmentioning
confidence: 99%
“…In most cases, in order to form the two-layer structure, various cross-linking technologies can oen be carried out, including chemical cross-linking, 18 UV-ozone cross-linking, 19 and plasma induced cross-linking. 20 In fact, the difference in molecule modulus between the top layer and lower layer, closely related to cross-linking intensity, can greatly inuence the nal pattern morphologies and kinetics. Furthermore, varying the external stress will prompt the emergence of diverse surface morphologies with different characteristic dimensions.…”
Section: Introductionmentioning
confidence: 99%